Financial Performance Analysis Based on Financial Ratios at PT Aneka Tambang Tbk - Sabda Dian Nurani Siahaan; Al Faiz; Muhammad Ridho Nawawi; Anita Putri Hermawan (Asian Journal of Applied Business and Management, 2023)
PT Aneka Tambang Tbk (ANTAM) is a mining company that processes a number of minerals and runs other businesses including trade and industry, transportation and other services related to the mining sector. This study aims to determine the financial performance of PT Aneka Tambang Tbk which is contained in the financial statements through the official website of PT Aneka Tambang. This study uses a quantitative descriptive approach using liquidity, solvency, activity and profitability ratios. The results of the research conducted showed that the financial performance of PT Aneka Tambang Tbk in 2018-2021 was not good because data on liquidity ratios, solvency, activity and profitability were below industry standard ratios. Thus it can be concluded that PT Aneka Tambang Tbk's finances fluctuated due to the difficulty in paying short-term and long-term liabilities.